Smallholders Oil Palm: Problems and Solutions - Valentina Sokoastri; Doni Setiadi; Arif Rakhman Hakim; Andre Dani Mawardhi; M Lukman Fadli (Sodality: Jurnal Sosiologi Pedesaan, 2019)
Forty percent of the total oil palm plantation area in Indonesia belong to the smallholder palm oil plantations. The productivity of smallholder oil palm plantations is still relatively low, only around 2-3 tons of CPO/ha/year under PBN dan PBS. The aim of this study is to identify internal dan external constraints that cause low productivity of smallholder oil palm dan the recommended solutions. This research was taken in Sanggau dan Sintang Regencies which are the largest areas of smallholder palm oil plantation in West Borneo. Data obtained were analyzed by SWOT. The results showed that there were four main strategies to increase productivity dan solve problems on oil palm plantation in Sanggau dan Sintang Regencies, namely, 1) intensifying technical training of oil palm cultivation to increase the farmers’ knowledge dan capabilities, 2) increasing the role dan ability of farmer institutions both farmer groups dan ‘koperasi’ in establishing cooperation with stakeholders dan in marketing fresh fruit bunch (FFB), 3) escalating the awareness dan understanding of farmers in using digital information technology to support their business activities on oil palm, dan 4) strengthening the government protection against middlemen.